VEGF ‐C is required for intestinal lymphatic vessel maintenance and lipid absorption - Harri Nurmi; Pipsa Saharinen; Georgia Zarkada; Wei Zheng; Marius R. Robciuc; Kari Alitalo (2015)
Report12 October 2015Open Access VEGF-C is required for intestinal lymphatic vessel maintenance and lipid absorption Harri Nurmi Harri Nurmi Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Pipsa Saharinen Pipsa Saharinen Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Georgia Zarkada Georgia Zarkada Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Wei Zheng Wei Zheng Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Marius R Robciuc Marius R Robciuc Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Kari Alitalo Corresponding Author Kari Alitalo Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Harri Nurmi Harri Nurmi Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Pipsa Saharinen Pipsa Saharinen Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Georgia Zarkada Georgia Zarkada Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Wei Zheng Wei Zheng Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Marius R Robciuc Marius R Robciuc Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Kari Alitalo Corresponding Author Kari Alitalo Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland Search for more papers by this author Author Information Harri Nurmi1, Pipsa Saharinen1, Georgia Zarkada1, Wei Zheng1, Marius R Robciuc1,‡ and Kari Alitalo 1,‡ 1Wihuri Research Institute and Translational Cancer Biology Program, Biomedicum Helsinki, University of Helsinki, Helsinki, Finland ‡These authors contributed equally to this work *Corresponding author. Tel: +358 2 941 25511, E-mail: [email protected] EMBO Mol Med (2015)7:1418-1425https://doi.org/10.15252/emmm.201505731 PDFDownload PDF of article text and main figures. Peer ReviewDownload a summary of the editorial decision process including editorial decision letters, reviewer comments and author responses to feedback. ToolsAdd to favoritesDownload CitationsTrack CitationsPermissions ShareFacebookTwitterLinked InMendeleyWechatReddit Figures & Info Abstract Vascular endothelial growth factor C (VEGF-C) binding to its tyrosine kinase receptor VEGFR-3 drives lymphatic vessel growth during development and in pathological processes. Although the VEGF-C/VEGFR-3 pathway provides a target for treatment of cancer and lymphedema, the physiological functions of VEGF-C in adult vasculature are unknown. We show here that VEGF-C is necessary for perinatal lymphangiogenesis, but required for adult lymphatic vessel maintenance only in the intestine. Following Vegfc gene deletion in adult mice, the intestinal lymphatic vessels, including the lacteal vessels, underwent gradual atrophy, which was aggravated when also Vegfd was deleted. VEGF-C was expressed by a subset of smooth muscle cells adjacent to the lacteals in the villus and in the intestinal wall. The Vegfc-deleted mice showed defective lipid absorption and increased fecal excretion of dietary cholesterol and fatty acids. When fed a high-fat diet, the Vegfc-deficient mice were resistant to obesity and had improved glucose metabolism. Our findings indicate that the lymphangiogenic growth factors provide trophic and dynamic regulation of the intestinal lymphatic vasculature, which could be especially important in the dietary regulation of adiposity and cholesterol metabolism. Synopsis A new mouse model allows effective, timed and long lasting deletion of vascular endothelial growth factor C (VEGF-C) by the Cre-Lox system and highlights its relevance for intestinal lymphatic vessel maintenance and lipid absorption. Vegfc deletion halted the growth of lymphatic vessels at all stages of development. In adults with a normally developed lymphatic system, Vegfc deficiency specifically induced intestinal lymphatic vessel atrophy. Lymphatic vessel atrophy in the adult intestine had no impact on animal welfare but reduced dietary lipid uptake and high fat diet-induced obesity. Introduction Lymphatic vessels regulate tissue fluid homeostasis, immune cell trafficking, and dietary fat absorption, and their malfunction leads to chronic edema and impaired immune responses (Cueni & Detmar, 2008; Alitalo, 2011; Koltowska et al, 2013). Lymphangiogenesis occurs during pathological processes such as inflammation and tumor metastasis and inhibitors of lymphangiogenic growth factors and their receptors are currently in clinical trials in human cancer patients (Alitalo, 2011). The development of the lymphatic vasculature is guided primarily by VEGF-C-mediated activation of VEGFR-3, which is the main VEGF receptor expressed by lymphatic endothelial cells (Makinen et al, 2001; Karkkainen et al, 2004). In the absence of VEGF-C, the development of lymphatic vessels is arrested during their initial spouting from embryonic veins (Karkkainen et al, 2004). VEGF-D, the second VEGFR-3 ligand, cannot compensate for the absence of VEGF-C during development, but it induces lymphangiogenesis when overexpressed and its deletion during development results in mild lymphatic vessel atrophy in the skin (Rissanen et al, 2003; Karkkainen et al, 2004; Alitalo, 2011; Paquet-Fifield et al, 2013; Astin et al, 2014). During the postnatal period, the lymphatic vessels continue to expand, and in the intestine, the lacteal vessels grow into the intestinal villi to facilitate lipid absorption from the fat-rich milk (Kim et al, 2007). Lipid absorption allowed Gaspare Aselli to discover lymphatic vessels by their content of milky fluid in the 17th century (Dixon, 2010). Recent studies have shown that the lacteal vessels are actively involved in lipid transport from the small intestinal epithelium to the lymphatic system and further to the blood circulation, although the detailed mechanisms have not been elucidated (Dixon, 2010). In several genetic mouse models of impaired lymphatic development, including Vegfr3 and Vegfc hypomorphic mice, and Chy mice that have a missense point mutation in Vegfr3, lipid-rich chylous ascites develops after birth but resolves before weaning (Karkkainen et al, 2001, 2004; Haiko et al, 2008). However, the possible function of lymphangiogenic growth factors in the normally developed adult intestine is not known. Here we have studied the role of VEGF-C in lymphatic vessel growth, maintenance, and function in neonatal and adult mice by using a mouse model that allows effective Vegfc gene deletion by the Cre-Lox system (Aspelund et al, 2014). We demonstrate that VEGF-C has a crucial role in the maintenance of the intestinal lymphatic vessels and dietary fat absorption. Results and Discussion Vegfc gene deletion arrests lymphatic vessel growth in the developing intestine In Vegfc gene-deleted embryos, lymphatic vessel sprouting from the major embryonic veins at embryonic day (E) 10.5 is arrested and the embryos die between E15.5 and E17.5 (Karkkainen et al, 2004). To study how the loss of VEGF-C affects lymphatic vessel development during the last trimester of fetal development, we crossed the Vegfcflox/flox mice (Aspelund et al, 2014) with mice expressing the universal deletor R26Cre-ERT2 (Ventura et al, 2007). To delete Vegfc in the R26Cre-ERT2;Vegfcflox/flox embryos, pregnant females were injected with 4-OH tamoxifen at E12.5 and E13.5. Analysis at E18.5 indicated that the Vegfc-deleted (VCiΔR26) embryos lack mesenteric lymphatic vessels either completely (data not shown) or exhibit lymphatic vessel fragments and blind-ended lymphatic stubs that extend toward the intestinal wall (Fig 1A and B). Deletion of Vegfc at E14.5 blocked the maturation of the mesenteric collecting lymphatic vessels. The developing vessels lacked valves and were much thinner than in the wild-type (WT) Vegfcflox/flox embryos (Fig 1C and D). In addition, the lymphatic vessels in the intestinal wall failed to develop in the VCiΔR26 embryos, whereas the blood vessels were not affected (Fig 1E–H). Figure 1. VEGF-C is required for lymphatic vessel growth in the developing intestine and for the intestinal lymphatic vessel maintenance in adult miceMice received tamoxifen as indicated in the figure. Immunofluorescence analyses from the intestine were performed in (A–H) embryos, (I–L) pups, and (M–U) adults. A–D. Mesenteric blood (PECAM1, red) and lymphatic vessels (LYVE1, green; PROX1, gray). Asterisks indicate lymphatic valves, arrow indicates a lymphatic vessel stub, and arrowhead indicates an isolated lymphatic vessel fragment E–H. Blood vessels (PECAM1, green) and lymphatic vessels (VEGFR-3, red) in the small intestinal wall. I, J. Detection of chylous ascites (arrows) in the VCiΔR26 mice at P6. K, L. LYVE1 staining of intestinal lymphatic vessels at P6. M–T. LYVE1 staining of lymphatic vessels in the intestinal wall in adult mice. Genotypes and deletion lengths are indicated in (U). U. Quantification of LYVE1 areas in (M–T). Length of the i∆Vegfc gene deletion is indicated in months (mo), and Vegfd indicates the VEGF-D genotype. Data are represented as mean ± SEM. Significant differences were determined using one-way ANOVA and Bonferroni post hoc analysis compared to WT intestine represented in (M). *P = 0.003, **P = 0.001, ***P = 0.0008, ♯P = 0.0002, §P = 0.0001. Data information: Scale bars: 200 μm in (A–H) and 400 μm in (K–T). n = 25 (M); 5 (N); 8 (O); 7 (P); 6 (Q); 5 (R); 6 (S); 3 (T). Download figure Download PowerPoint Lacteal lymphatic vessels develop after birth and are involved in the absorption of dietary lipids from milk (Kim et al, 2007). In order to determine whether VEGF-C is necessary for the formation of lacteal vessels, we deleted Vegfc by daily 4-OH tamoxifen injections to VCiΔR26 and WT pups from postnatal day 1 (P1) to P4. Upon necropsy at P6, chylous ascites was observed in the VCiΔR26 pups, but not in the WT littermates (Fig 1I and J). Immunofluorescence staining of intestinal cross sections at P6 revealed that the lacteal vessels failed to develop in the VCiΔR26 pups (Fig 1K and L and Appendix Fig S1A and B). Lymphatic vessels of the intestinal wall, which develop during the intrauterine period, failed to expand upon Vegfc deletion in postnatal period (Appendix Fig S1C–H). The lymphatic vessel density in the skin was also reduced in the VCiΔR26 pups when compared to their WT littermates (Appendix Fig S1I and J), whereas no changes were observed in the blood vessel density (Appendix Fig S1K and L). Taken together, these results indicate that VEGF-C is required for developmental and early postnatal lymphangiogenesis. VEGF-C is needed for lymphatic vessel maintenance only in the intestine The VCiΔR26 mouse model allowed us to determine the role of VEGF-C in the maintenance of lymphatic vessels in adult mice. To induce Vegfc gene deletion, we administered tamoxifen to the mice starting at 8 weeks of age. Real-time PCR analysis of several tissues indicated that Vegfc mRNA levels in VCiΔR26 mice were reduced to 2–15% of the levels in WT mice 3 months after tamoxifen treatment (Appendix Table S1). Notably, whole-mount LYVE1 staining revealed that the lymphatic vessels of the intestinal wall undergo a gradual atrophy in the VCiΔR26 mice (Fig 1M–U). Shorter lacteals were observed already 3 weeks after Vegfc gene deletion (Appendix Fig S2A), and after 3 months, the lacteals were strikingly thinner and shorter, containing a reduced number of lymphatic endothelial cells, suggesting that vessel atrophy was due to cell loss (Appendix Fig S2B). Thus, the lymphatic vessel atrophy started from lacteals and then progressed to the lymphatic network in the intestinal wall. In contrast, even when Vegfc was effectively deleted for 6 months, there were no changes in lymphatic vessel density in the lymph nodes, ears, or trachea (Appendix Fig S3A–E). The development of the lymphatic vasculature relies principally on VEGF-C/VEGFR-3 signaling, while VEGF-D, the other known ligand for VEGFR-3, cannot compensate for the lack of VEGF-C signaling in Vegfc−/− embryos (Karkkainen et al, 2004). Yet, VEGF-D was found to induce lymphangiogenesis when overexpressed in mouse tissues (Veikkola et al, 2001; Baluk et al, 2005). Constitutive deletion of Vegfd had no effect on lymphatic vasculature in the adult mouse intestine, in agreement with previous reports (Fig 1U) (Baldwin et al, 2005). Surprisingly, however, conditional deletion of Vegfc in the Vegfd−/− mice resulted in more severe atrophy of the intestinal lymphatic vessels than Vegfc deletion alone (Fig 1M–U). These data indicate that VEGF-C is the primary trophic signal for the maintenance of the intestinal lymphatic vessels, but VEGF-D can partially compensate for the absence of VEGF-C. Because we did not observe changes in Vegfd mRNA expression levels upon Vegfc deletion (WT = 1.02 ± SEM 0.14 vs. VCiΔR26 = 0.98 ± SEM 0.16), it is likely that increased bioactive VEGF-D or increased VEGF-D binding to VEGFR-3 partially compensates for the loss of VEGF-C. VEGF-C is expressed by a subset of smooth muscle cells in the intestine Next, we sought to identify the cell types that express VEGF-C in the adult intestine. Previous work from our laboratory showed that VEGF-C is expressed in arterial smooth muscle cells (SMCs) both in mice and humans (Partanen et al, 2000; Paavonen et al, 2002; Karkkainen et al, 2004). To define the cells expressing VEGF-C and its receptors, we performed β-Gal staining of intestines from Vegfc/LacZ (Karkkainen et al, 2004), Vegfr3/LacZ (Dumont et al, 1998), and Vegfr2/LacZ (Shalaby et al, 1995) mice. VEGF-C staining in the villi was weak in comparison with VEGFR-3 and VEGFR-2 stainings, in lymphatic and blood vessels, respectively (Fig 2A and B). Higher resolution analysis combined with immunohistochemistry demonstrated VEGF-C expression in SMCs, in the inner circular muscle layer of the intestinal wall, in arterial smooth muscle, and in a subset of the SMC fibers in the villus (Fig 2C). In the villi, the VEGF-C β-Gal signal was most prominent adjacent to the LYVE1-counterstained lymphatic vessels (Fig 2D). The intestinal wall of the Vegfc/LacZ mice showed a prominent arterial β-Gal staining pattern, which was further analyzed by PECAM-1 counterstaining of cross sections (Fig 2E), which confirmed VEGF-C expression in the arterial SMCs. Whole-mount confocal microscopy showed a close contact between the lacteal vessels and the SMC fibers in the basal part of the villus where also β-Gal staining of VEGF-C was detected (Fig 2D and F). These results suggest that SMCs in the villi and in the intestinal wall provide an important source for VEGF-C, which is required to maintain the lymphatic vessel architecture in the intestine. It should be noted that SMC contractility in the villi has been suggested to be important for dietary lipid absorption and that VEGF-C can induce contraction of the SMCs around the collecting lymphatic vessels in normal and pathological conditions (Hosoyamada & Sakai, 2005, 2007; Breslin et al, 2007; Gogineni et al, 2013). Figure 2. Smooth muscle cells are the main source of VEGF-C in adult intestine Overview of the small intestine cross section stained with nuclear red and highlighting the location of higher magnification images in (B–F); (I) for the entire villus and (II) for the villus base. β-Gal staining pattern of the villus in wild-type (Ctrl), Vegfc/LacZ (VC), Vegfr3/LacZ (VR-3), and Vegfr2/LacZ (VR-2) mice. Higher magnification images representing β-Gal staining of the villus base in Vegfc/LacZ mice. Vegfc/LacZ β-Gal staining reaction with smooth muscle actin (SMA) peroxidase staining. Vegfc/LacZ β-Gal staining and LYVE1 peroxidase staining. Surface image of Vegfc/LacZ β-Gal-stained intestine (left) and cross section counterstaining with PECAM1 (right). Immunofluorescence staining of lacteal lymphatic vessel (LYVE1), blood capillaries (PECAM1), and smooth muscle cells (SMA). Data information: Arrows indicate the VEGF-C expression in arterial SMC, arrowheads indicate the VEGF-C expression in SMC fibers in the villus, and asterisks highlight the VEGF-C expression in circular smooth muscle cell layer of the intestinal wall. Scale bars: 50 μm, except (C) inset 25 μm. Download figure Download PowerPoint To determine whether the effect of VEGF-C on intestinal lymphatic vessels is dependent on VEGFR-3, we analyzed the Rosa26CreERT2;Vegr3flox/flox (R3iΔR26) mouse model (Haiko et al, 2008). As expected, deletion of Vegfr3 for 3 months induced lacteal vessel regression, similar to VEGF-C deletion (Appendix Fig S4A and B). However, lymphatic vessel density in the intestinal wall was not altered, suggesting that VEGF-C can signal via VEGFR-2 to stabilize the lymphatic plexus. We have previously shown that the tyrosine kinase inhibitor cediranib inhibits lymphangiogenesis induced by adenoviral VEGF-C delivery into adult mouse skin (Heckman et al, 2008). However, administration of the tyrosine kinase inhibitor sunitinib at doses that block VEGFR-2 and VEGFR-3 (Ki: VEGFR-3 17 nM/VEGFR-2 9 nM) (Faivre et al, 2007) had no effect on the lacteal vessels, although sunitinib significantly reduced blood vessel density in the intestinal villi (Appendix Fig S4C–E), in line with a previous report (Kamba et al, 2006). Thus, lacteal vessels appear to be more resistant than blood vessels in the intestinal villus toward VEGFR tyrosine kinase inhibition. Vegfc deletion reduces lipid absorption, inducing resistance to diet-induced obesity To determine whether VEGF-C is important for lipid absorption by the intestinal lymphatic vessels, we performed an oral fat tolerance test in mice in which VEGF-C had been deleted 3 months earlier. The clearance of triglycerides from plasma was blocked by injection of Triton WR 1339, an inhibitor of lipoprotein lipase activity (Otway & Robinson, 1967). Analysis of triglyceride levels in serum after the administration of an oil bolus showed that the VCiΔR26 mice have impaired lipid absorption when compared to WT mice (Appendix Fig S5A). Although these results correlate with the lacteal regression, we cannot exclude the involvement of possible other effects of Vegfc deletion. We further studied whether the reduction in dietary lipid absorption observed in the VCiΔR26 mice has an impact on diet-induced obesity in mice fed high-fat diet (HFD). Initial experiments in the 129SV/C57Bl/6J mixed genetic background did not reveal major differences in body weight, but indicated that the VCiΔR26 mice have an improved glucose metabolism compared to WT mice (Appendix Fig S5B and C). Interestingly, in the mixed background, the Vegfc-deleted mice had reduced serum cholesterol levels, whereas fecal cholesterol and free fatty acid (FFA) levels were increased in the VCiΔR26 mice, indicating impaired dietary lipid absorption (Appendix Fig S5D). We further performed HFD feeding experiments in the pure C57Bl/6J background, an established model of diet-induced obesity. We deleted Vegfc in 8-week-old male mice and started HFD feeding 4 weeks later. The VCiΔR26 mice gained significantly less weight and had better glucose tolerance than their WT littermates, independently of concurrent Vegfd deletion (Fig 3A–C and Appendix Fig S5E and F). At necropsy after HFD, very low amounts of chyle were detected in one out of 16 Vegfc-deleted mice and in two out of five Vegfc- plus Vegfd-deleted mice, indicating mild lymphatic leakage. Body composition analysis showed that the VCiΔR26 mice had a significant reduction in total fat weight and fat percentage, but no changes in lean weight in comparison with WT littermates (Fig 3D and Appendix Fig S5G). The changes in fat accumulation could not be explained by reduced caloric intake, since food consumption was similar between the VCiΔR26 and WT mice (Fig 3E). As expected on the basis of our results from the mixed background, Vegfc deletion induced intestinal lymphatic vessel atrophy and increased lipid excretion into the feces also in the C57Bl/6J background (Fig 3F–H). No difference in body weight was observed between WT and Vegfc-deleted mice on regular diet in which the majority of calories are derived from carbohydrate. This further indicates that the reduced body weight of the Vegfc-deleted mice on HFD is a result of reduced dietary lipid absorption. Figure 3. Intestinal lymphatic vessel regression leads to impaired lipid absorption and resistance to diet-induced obesityTwo-month-old mice received tamoxifen and were fed on high-fat diet (HFD) for seven weeks before analysis. Body weight change during seven weeks of HFD, expressed as average fold change in comparison with the starting weight. n = 16, WT; n = 6, Vegfd−/−; n = 16, VCiΔR26; n = 5, Vegfd−/−; VCiΔR26. Body weight comparisons at seven weeks of HFD. Significant differences were determined using one-way ANOVA and Bonferroni post hoc analysis compared to WT. *P = 0.004; **P = 0.003. n = 16, WT; n = 6, Vegfd−/−; n = 16, VCiΔR26; n = 5, Vegfd−/−; VCiΔR26. Glucose tolerance test (GTT) after six weeks of HFD. Significant differences were determined using unpaired two-tailed t-test. *P = 0.014; **P = 0.041. n = 5, WT; n = 6, VCiΔR26. Total fat weight, fat percentage from body composition measurements after six weeks of HFD, and weights of visceral fat (VF) and subcutaneous fat (SF) at the time of necropsy. Significant differences were determined using unpaired two-tailed t-test. *P = 0.006; **P = 0.001; #P = 0.008; §P = 0.006. n = 4 in each group. Food consumption during the fifth week of HFD. n = 9, WT; n = 10, VCiΔR26. Whole-mount immunofluorescence staining of blood (PECAM1, red) and lymphatic vessels (LYVE1, green) in intestinal villi and intestinal wall. Quantification of the lacteal and villus length (solid and striped color bars, respectively) and the intestinal wall LYVE1+ area percentage from images represented in (F). Significant differences were determined using unpaired two-tailed t-test. *P = 0.0002; **P = 0.00007. n = 5, WT; n = 6, VCiΔR26. Free fatty acid (FFA) and cholesterol measurements from the feces after six weeks of HFD. Significant differences were determined using unpaired two-tailed t-test. *P = 0.001; **P = 0.007. n = 5, WT; n = 6, VCiΔR26. Data information: Scale bars: 100 μm (villi) and 300 μm (intestinal wall). Data are represented as mean ± SEM. Download figure Download PowerPoint Use of the newly established Vegfc gene targeted mouse model allowed us to determine the effect of chronic VEGF-C deficiency in adult mice, where lymphatic vasculature is normally in a quiescent state (Aspelund et al, 2014). The results of this study show that intestinal lymphatic vessels in adults require trophic signals from VEGF-C and that VEGF-D can only partially compensate for the loss of VEGF-C to maintain their structure and function. The unexpected finding that VEGF-C blockade affects only intestinal lymphatic vasculature and lipid absorption may provide new therapeutic opportunities. The specific VEGF-C/VEGFR-3 inhibitors that are currently in phase I clinical trials for cancer treatment could provide additional benefit for the treatment of obesity and cardiovascular disease by reducing the absorption of excess dietary lipids. Further studies should address lacteal vessel atrophy and dietary fat absorption in clinical trials employing VEGF-C/VEGFR-3 blocking therapeutics. Materials and Methods Study approval National Animal Experiment Board in Finland approved all experiments involving the use of mice. Mice and tissues The mouse lines Vegfcfl/fl (Aspelund et al, 2014), Vegfr3fl/fl (Haiko et al, 2008), Rosa26-CreERT2 (Ventura et al, 2007), Vegfd (Baldwin et al, 2005), Vegfc/LacZ (Karkkainen et al, 2004), Vegfr3/LacZ (Dumont et al, 1998), and Vegfr2/LacZ (Shalaby et al, 1995) have been described previously. We used VCiΔR26 mice in the mixed C57Bl/6J and 129SV background or after backcrossing to the C57Bl/6J strain for at least 7 generations. For induction of Cre-mediated recombination in embryos, the mother was injected at the indicated days with two consecutive intragastric doses of 4-OH tamoxifen (4-OHT) (Sigma) (25 mg/ml dissolved in 100 μl ethanol/olive oil). In the neonatal VCiΔR26 or WT mice, the Cre-mediated recombination was induced between P1 and P4 by daily intragastric administration of 2 μl 4-OHT (25 mg/ml dissolved in ethanol). Recombination in adult mice (7–8 weeks old) was done by intragastric tamoxifen (Sigma, dissolved in corn oil at 2 mg/ml, 100 μl) administration during five consecutive days. Detailed animal experiment information can be found in the Appendix Supplementary Materials and Methods. Statistics Quantitative data were compared between groups by two-tailed unpaired t-test or one-way ANOVA followed by Bonferroni post hoc test for multiple comparisons. Values are expressed as mean ± SEM. P-value < 0.05 was considered significant. Acknowledgements We thank Jarmo Koponen, Essi Salminen, Maija Atuegwu, Mari Jokinen, Tapio Tainola, and Kirsi Mänttäri for technical assistance, the personnel of the Biomedicum Imaging Unit for microscopy service and the Laboratory Animal Center of the University of Helsinki for animal housing. This study was supported in part by the Leducq Transatlantic Network of Excellence in Lymph Vessels in Obesity and Cardiovascular Disease (grant no: 11CVD03), the Marie Curie ITN Vessel consortium (grant no: 317250) of the Seventh Framework Program of European Union, Academy of Finland Centre of Excellence in Translational Cancer Biology 2014-2019 (grant no: 271845), the European Research Council (ERC-2010-AdG-268804); the Finnish Cancer Research Organizations, the Sigrid Juselius Foundation, and by the Biomedicum Helsinki Foundation and Ida Montin Foundation (to H.N.). Author contributions HN and MRR designed and performed experiments, data acquisition, analysis and interpretation of data, and wrote the manuscript; PS designed and produced the VCiΔR26 mice; GZ and WZ performed experiments; and KA designed experiments, conducted scientific direction, and wrote the manuscript. Conflict of interest The authors declare that they have no conflict of interest. The paper explained Problem Specific VEGF-C/VEGFR-3 inhibitors are currently in phase I clinical trials for cancer treatment, but the effects of long-term inhibition of these pathways in adults are still incompletely known. Preclinical long-term follow-up studies of VEGF-C/VEGFR-3 signaling deficiency are now possible by using the novel mouse model that allows effective Vegfc gene deletion by the Cre-Lox system. This eliminates the confounding effects of developmental defects observed in previous mouse models. Results The mouse model used in this study allowed effective, timed, and long-lasting gene deletion of Vegfc. Surprisingly, in adults with normally developed lymphatic system, Vegfc was required only for the maintenance of intestinal lymphatic vessel structure and function. Regression of lymphatic vessels in the intestine induced by Vegfc deletion had no effects on animal welfare but protected the mice from the obesogenic effect of excessive dietary lipid uptake. Impact Long-term inhibition of VEGF-C/VEGFR-3 is very well tolerated in animal models. VEGF-C blockade induces atrophy of intestinal lymphatic vessels and inhibits dietary lipid absorption, which could provide new therapeutic opportunities for the treatment of obesity and cardiovascular diseases. Supporting Information Appendix (PDF document, 13.7 MB) Review Process File (PDF document, 470.5 KB) References Alitalo K (2011) The lymphatic vasculature in disease. Nat Med 17: 1371–1380CrossrefCASPubMedWeb of Science®Google Scholar Aspelund A, Tammela T, Antila S, Nurmi H, Leppanen VM, Zarkada G, Stanczuk L, Francois M, Makinen T, Saharinen P et al (2014) The Schlemm's canal is a VEGF-C/VEGFR-3-responsive lymphatic-like vessel. J Clin Invest 124: 3975–3986CrossrefCASPubMedWeb of Science®Google Scholar Astin JW, Haggerty MJ, Okuda KS, Le Guen L, Misa JP, Tromp A, Hogan BM, Crosier KE, Crosier PS (2014) Vegfd can compensate for loss of Vegfc in zebrafish facial lymphatic sprouting. Development 141: 2680–2690CrossrefCASPubMedWeb of Science®Google Scholar Baldwin ME, Halford MM, Roufail S, Williams RA, Hibbs ML, Grail D, Kubo H, Stacker SA, Achen MG (2005) Vascular endothelial growth factor D is dispensable for development of the lymphatic system. Mol Cell Biol 25: 2441–2449CrossrefCASPubMedWeb of Science®Google Scholar Baluk P, Tammela T, Ator E, Lyubynska N, Achen MG, Hicklin DJ, Jeltsch M, Petrova TV, Pytowski B, Stacker SA et al (2005) Pathogenesis of persistent lymphatic vessel hyperplasia in chronic airway inflammation. J Clin Invest 115: 247–257CrossrefCASPubMedWeb of Science®Google Scholar Breslin JW, Gaudreault N, Watson KD, Reynoso R, Yuan SY, Wu MH (2007) Vascular endothelial growth factor-C stimulates the lymphatic pump by a VEGF receptor-3-dependent mechanism. Am J Physiol Heart Circ Physiol 293: H709–H718CrossrefCASPubMedWeb of Science®Google Scholar Cueni LN, Detmar M (2008) The lymphatic system in health and disease. Lymphat Res Biol 6: 109–122CrossrefPubMedGoogle Scholar Dixon JB (2010) Lymphatic lipid transport: sewer or subway? Trends Endocrinol Metab 21: 480–487CrossrefCASPubMedWeb of Science®Google Scholar Dumont DJ, Jussila L, Taipale J, Lymboussaki A, Mustonen T, Pajusola K, Breitman M, Alitalo K (1998) Cardiovascular failure in mouse embryos deficient in VEGF receptor-3. Science 282: 946–949CrossrefCASPubMedWeb of Science®Google Scholar Faivre S, Demetri G, Sargent W, Raymond E (2007) Molecular basis for sunitinib efficacy and future clinical development. Nat Rev Drug Discov 6: 734–745CrossrefCASPubMedWeb of Science®Google Scholar Gogineni A, Caunt M, Crow A, Lee CV, Fuh G, van Bruggen N, Ye W, Weimer RM (2013) Inhibition of VEGF-C modulates distal lymphatic remodeling and secondary metastasis. PLoS ONE 8: e68755CrossrefCASPubMedWeb of Science®Google Scholar Haiko P, Makinen T, Keskitalo S, Taipale J, Karkkainen MJ, Baldwin ME, Stacker SA, Achen MG, Alitalo K (2008) Deletion of vascular endothelial growth factor C (VEGF-C) and VEGF-D is not equivalent to VEGF receptor 3 deletion in mouse embryos. Mol Cell Biol 28: 4843–4850CrossrefCASPubMedWeb of Science®Google Scholar Heckman CA, Holopainen T, Wirzenius M, Keskitalo S, Jeltsch M, Yla-Herttuala S, Wedge SR, Jurgensmeier JM, Alitalo K (2008) The tyrosine kinase inhibitor cediranib blocks ligand-induced vascular endothelial growth factor receptor-3 activity and lymphangiogenesis. Cancer Res 68: 4754–4762CrossrefCASPubMedWeb of Science®Google Scholar Hosoyamada Y, Sakai T (2005) Structural and mechanical architecture of the intestinal villi and crypts in the rat intestine: integrative reevaluation from ultrastructural analysis. Anat Embryol 210: 1–12CrossrefPubMedWeb of Science®Google Scholar Hosoyamada Y, Sakai T (2007) Mechanical components of rat intestinal villi as revealed by ultrastructural analysis with special reference to the axial smooth muscle cells in the villi. Arch Histol Cytol 70: 107–116CrossrefPubMedWeb of Science®Google Scholar Kamba T, Tam BY, Hashizume H, Haskell A, Sennino B, Mancuso MR, Norberg SM, O'Brien SM, Davis RB, Gowen LC et al (2006) VEGF-dependent plasticity of fenestrated capillaries in the normal adult microvasculature. Am J Physiol Heart Circ Physiol 290: H560–H576CrossrefCASPubMedWeb of Science®Google Scholar Karkkainen MJ, Haiko P, Sainio K, Partanen J, Taipale J, Petrova TV, Jeltsch M, Jackson DG, Talikka M, Rauvala H et al (2004) Vascular endothelial growth factor C is required for sprouting of the first lymphatic vessels from embryonic veins. Nat Immunol 5: 74–80CrossrefCASPubMedWeb of Science®Google Scholar Karkkainen MJ, Saaristo A, Jussila L, Karila KA, Lawrence EC, Pajusola K, Bueler H, Eichmann A, Kauppinen R, Kettunen MI et al (2001) A model for gene therapy of human hereditary lymphedema. Proc Natl Acad Sci USA 98: 12677–12682CrossrefCASPubMedWeb of Science®Google Scholar Kim KE, Sung HK, Koh GY (2007) Lymphatic development in mouse small intestine. Dev Dyn 236: 2020–2025Wiley Online LibraryCASPubMedWeb of Science®Google Scholar Koltowska K, Betterman KL, Harvey NL, Hogan BM (2013) Getting out and about: the emergence and morphogenesis of the vertebrate lymphatic vasculature. Development 140: 1857–1870CrossrefCASPubMedWeb of Science®Google Scholar Makinen T, Veikkola T, Mustjoki S, Karpanen T, Catimel B, Nice EC, Wise L, Mercer A, Kowalski H, Kerjaschki D et al (2001) Isolated lymphatic endothelial cells transduce growth, survival and migratory signals via the VEGF-C/D receptor VEGFR-3. EMBO J 20: 4762–4773Wiley Online LibraryCASPubMedWeb of Science®Google Scholar Otway S, Robinson DS (1967) The effect of a non-ionic detergent (Triton WR 1339) on the removal of triglyceride fatty acids from the blood of the rat. J Physiol 190: 309–319Wiley Online LibraryCASPubMedWeb of Science®Google Scholar Paavonen K, Mandelin J, Partanen T, Jussila L, Li TF, Ristimaki A, Alitalo K, Konttinen YT (2002) Vascular endothelial growth factors C and D and their VEGFR-2 and 3 receptors in blood and lymphatic vessels in healthy and arthritic synovium. J Rheumatol 29: 39–45CASPubMedWeb of Science®Google Scholar Paquet-Fifield S, Levy SM, Sato T, Shayan R, Karnezis T, Davydova N, Nowell CJ, Roufail S, Ma GZ, Zhang YF et al (2013) Vascular endothelial growth factor-d modulates caliber and function of initial lymphatics in the dermis. J Invest Dermatol 133: 2074–2084CrossrefCASPubMedWeb of Science®Google Scholar Partanen TA, Arola J, Saaristo A, Jussila L, Ora A, Miettinen M, Stacker SA, Achen MG, Alitalo K (2000) VEGF-C and VEGF-D expression in neuroendocrine cells and their receptor, VEGFR-3, in fenestrated blood vessels in human tissues. FASEB J 14: 2087–2096Wiley Online LibraryCASPubMedWeb of Science®Google Scholar Rissanen TT, Markkanen JE, Gruchala M, Heikura T, Puranen A, Kettunen MI, Kholova I, Kauppinen RA, Achen MG, Stacker SA et al (2003) VEGF-D is the strongest angiogenic and lymphangiogenic effector among VEGFs delivered into skeletal muscle via adenoviruses. Circ Res 92: 1098–1106CrossrefCASPubMedWeb of Science®Google Scholar Shalaby F, Rossant J, Yamaguchi TP, Gertsenstein M, Wu XF, Breitman ML, Schuh AC (1995) Failure of blood-island formation and vasculogenesis in Flk-1-deficient mice. Nature 376: 62–66CrossrefCASPubMedWeb of Science®Google Scholar Veikkola T, Jussila L, Makinen T, Karpanen T, Jeltsch M, Petrova TV, Kubo H, Thurston G, McDonald DM, Achen MG et al (2001) Signalling via vascular endothelial growth factor receptor-3 is sufficient for lymphangiogenesis in transgenic mice. EMBO J 20: 1223–1231Wiley Online LibraryCASPubMedWeb of Science®Google Scholar Ventura A, Kirsch DG, McLaughlin ME, Tuveson DA, Grimm J, Lintault L, Newman J, Reczek EE, Weissleder R, Jacks T (2007) Restoration of p53 function leads to tumour regression in vivo. Nature 445: 661–665CrossrefCASPubMedWeb of Science®Google Scholar Previous ArticleNext Article Read MoreAbout the coverClose modalView large imageVolume 7,Issue 11,November 2015Cover: This month's cover highlights the Research Article " VEGF-C is required for intestinal lymphatic vessel maintenance and lipid absorption" by Harri Nurmi, Marius R. Robciuc, Kari Alitalo and colleagues. The composite image shows the lacteal lymphatic vessel (green) and surrounding smooth muscle fibers (red) within a villus of the small intestine. Green autofluorescence was enhanced at the villus border to highlight the enterocytes. © Cover image by Marius R. Robciuc, Wihuri Research Institute and Translational Cancer Biology Program, University of Helsinki, Finland. Volume 7Issue 111 November 2015In this issue FiguresReferencesRelatedDetailsLoading ...